STRATEGI PEMULIHAN REMAJA YANG KECANDUAN JUDI ONLINE - Natanael Manullang; Philpresdo Simatupang; Dimas Giraldo Purba; Kevin Martin Sijabat; Reza Fahlevi Marbun; Dorlan Naibaho (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
The era of the Industrial Revolution 4.0 has significantly impacted various aspects of life, including adolescent behavior patterns and social interactions. The widespread access to the internet has facilitated numerous areas such as education, economy, and communication. However, technological advancements also pose risks, one of which is the increasing prevalence of online gambling among teenagers. This study aims to explore online gambling addiction in student A (16 years old) at SMA N 1 Siempat Nempu Hilir and the factors influencing it. The methodology employed is a single case study using a cognitive-behavioral therapy (CBT) approach integrated with biblical principles. Research instruments include pre- and post-intervention questionnaires on gambling behavior, psychological well-being, and parental supervision, as well as interviews with student A's close friends.The findings indicate that a lack of parental supervision is a primary factor contributing to online gambling addiction in student A. Through biblically-based CBT interventions, there was a significant reduction in the frequency and intensity of online gambling activities, an improvement in psychological well-being, and increased parental involvement in monitoring the child's activities. This study highlights the importance of a holistic approach that integrates psychological and spiritual aspects in addressing online gambling addiction among teenagers.To address and prevent the spread of online gambling addiction, cooperation between the community, government, and stakeholders is essential. Effective prevention efforts should include education on the risks and negative impacts of online gambling, enhanced parental supervision, and the provision of psychological and spiritual support for teenagers. By doing so, we can protect young people from the dangers of online gambling addiction and build a better future.